Efeitos do potencial alelopático de três leguminosas forrageiras sobre três invasoras de pastagens - Souza Filho, Antonio Pedro Da S.; Rodrigues, Luis Roberto de A.; Rodrigues, Teresinha de Jesus D. [UNESP] (My University, 1997)
Bioassays were carried out to identify and characterize the allelopathic potential effects of forage legumes leucena (Leucaena leucocephala), mineirão (Stylosanthes guianensis cv. Mineirão) and calopogônio (Calopogonium mucunoides) on germination and radicle elongation of the pasture weeds desmódio (Desmodium adscendens), guanxuma (Sida rhombifolia) and assa-peixe (Vernonia polyanthes). Aqueous seeds and shoot extracts were prepared in a concentration of 10% (w/v). The pH and osmotic potential were measured in each extract. The effects of the osmotic potential on the results were calculated considering the regression equations adjusted to the variations of osmotic potential in each parameter and the osmotic potential of the extracts. The results showed that the pH did not constitute in a source of variation of the results. The donor species indicated allelopathic potential that varied in function of donor and receiver species and part of the donor plant. The aqueous shoot extract of mineirão and calopogônio showed inhibition potential higher than the extract from seeds, while for leucena the effects more evident were obtained with the extract from seeds. Comparatively, the radicle elongation was a more sensitive indicator than germination to the effects of the extracts.The receiver species assa-peixe was the less sensitive to the effects of the extract.

Bioensaios foram desenvolvidos para identificar e caracterizar os efeitos do potencial alelopático das leguminosas forrageiras leucena, mineirão e calopogônio sobre a germinação e o alongamento da radícula das invasoras de pastagens desmódio, guanxuma e assa-peixe. Extratos aquosos de sementes e da parte aérea foram preparados na concentração de 10% (p/v). O pH e o potencial osmótico foram medidos em cada extrato. Os efeitos do potencial osmótico foram calculados pela equação de regressão, que se ajustou à variação do potencial osmótico em cada parâmetro, e pelo potencial osmótico dos extratos. Os resultados indicaram que o pH não constituiu em fonte de variação dos resultados. As espécies doadoras evidenciaram potencialidades alelopáticas que variaram em decorrência da espécie e da parte da planta doadora, bem como da receptora. Os extratos aquosos da parte aérea do mineirão e do calopogônio apresentaram potencialidades inibitórias superiores aos dos extratos das sementes, enquanto com leucena os efeitos mais marcantes foram obtidos com o extrato das sementes. Comparativamente, o alongamento da radícula foi um indicador mais sensível aos efeitos dos extratos do que a germinação. Das espécies receptoras, o assa-peixe foi a que evidenciou menor sensibilidade aos efeitos dos extratos.
Allelopathic potential of three forage legumes on three pasture weeds
Keywords: Allelopathy; Calopogonium; Desmodium; Leucena; Mineirão; Seed; Shoot; Sida rhombifolia; Vernonia polyanthes